Hybrid rice technology development: Ensuring China’s food security - Li, Jiming; Xin, Yeyun; Yuan, Longping (International Food Policy Research Institute, 2009)
China has used hybrid rice technology to help feed more than 20 percent of the world’s population using just 10 percent of the world’s total arable land. Hybrid rice allowed for a 14 percent reduction in total rice-growing acreage since 1978, while total rice production has increased 44.1 percent. Yield increases have helped China feed an extra 60 million people every year. Hybrid rice also has contributed to improved food security in China, which has limited the increase in global rice prices to the benefit of poor consumers in other countries. China’s rice breeders began hybrid development in 1964 using a three-line system. By 1976 China started large-scale commercial production of the three-line hybrid rice. In 1995, China successfully commercialized the two-line hybrid rice technology, and by 2002 the total area under two-line hybrid rice occupied 3.3 million ha, or 22 percent of the hybrid rice acreage. In 2000, the “super hybrid rice breeding” Phase I objective of 10.5 t/ha was attained, and the Phase II objective of 12 t/ha was accomplished in 2004. China’s hybrid rice seed production yields rose from 450 kg/ha in the late 1970s to 3.75 t/ha in 2008. This has ensured the quantity of commercial seed and lowered costs. The Chinese government provided critical support to the hybrid rice program through funding and policies. Government policies, standards, and investments in human resources and necessary infrastructure made hybrid rice attractive, profitable, and sustainable. To ensure the continued success of the hybrid rice program, further advances in biotechnology will be crucial for overcoming the challenges from increasing biotic or abiotic pressure, including the ever-decreasing water supply and more severe drought from global warming.